Vitamin D status in breast cancer cases following chemotherapy: A pre and post observational study in a tertiary hospital in Yogyakarta, Indonesia - Puspitaningtyas, Herindita; Sulistyoningrum, Dian Caturini; Witaningrum, Riani; Widodo, Irianiwati; Hardianti, Mardiah Suci; Taroeno-Hariadi, Kartika Widayati; Kurnianda, Johan; Purwanto, Ibnu; Hutajulu, Susanna Hilda (PLOS, 2022)
Objectives: To observe pre- and post-treatment vitamin D level and its association with treatment and concomitant factors in breast cancer patients treated with chemotherapy. Methods We performed a pre-post observational analysis that nested in an ongoing prospective cohort study of breast cancer patients at Dr. Sardjito General Hospital, Yogyakarta, Indonesia. 136 subjects were recruited from the main study. Information on subjects’ socio-demographic characteristics clinical status, and tumour profile was assessed at baseline. Number of chemotherapy cycles and chemotherapy-induced nausea vomiting (CINV) were also recorded. Vitamin D concentration was measured using ELISA methods at baseline and post-treatment. Vitamin D level of <20 ng/ml and <12 ng/ml were defined as deficiency and severe deficiency. Correlation between socio-demographic and clinical profile with baseline vitamin D was tested using Spearman correlation. Paired t-test was used to evaluate changes in post-treatment vitamin D concentration. The odds ratio for a subject to experience post-treatment vitamin D decrease was assessed based on number of chemotherapy cycles and CINV severity. Results: The mean vitamin D level before chemotherapy was very low (8.80±3.64 ng/ml) in the whole panel. Higher AST level were associated with lower vitamin D level at baseline (r = -0.188, p= 0.028). Severe deficiency was found in 82.4% subjects at baseline and the rate increased to 89.0% after chemotherapy. Eighty-five cases showed a decrease level whereas 51 showed a slight improvement. Overall, a significant decrease of the vitamin D level was observed after chemotherapy (median change 3.13±4.03 ng/ml, p <0.001). Subjects who received >6 cycles of chemotherapy were less likely to experience a decreased level of post-treatment vitamin D (OR = 0.436, 95% CI = 0.196–0.968, p = 0.039). Conclusions: Indonesian breast cancer patients showed pre-existing severe vitamin D deficiency and deterioration of vitamin D after chemotherapy. Future research is needed to explore its implication towards patients’ survival in the local setting. Evidence-based approach also needs to be taken to address this modifiable condition, including increasing awareness of the importance of maintaining vitamin D sufficiency both in patients and the general population.